Chemical reactions inside carbon nanotubes - Miners, Scott A. (2016)
The work presented in this thesis describes the development and application of strategies to evaluate the influence of extreme confinement within narrow single-walled carbon nanotubes (SWNT) on the pathways of preparative chemical reactions. Methodologies to reduce carbon nanotube length were critically assessed in order to aid the access and egress of reactants and products to and from the SWNT internal channel during confined reactions. A reliable procedure for the encapsulation of organic molecules within carbon nanotubes was developed utilising a novel fractional distillation procedure which exploits the effect of nanoscale confinement on the phase behaviour of liquids. Confinement of the halogenation of N-phenylacetamide within SWNT demonstrated, for the first time, that narrow SWNT are effective hosts for chemical reactions on a preparative scale in the absence of metallic catalysts. The selective formation of the para-brominated regioisomer improved from 68 to 97% as a direct result of confinement. Furthermore, the confinement of a range of azide-alkyne 1,3-dipolar cycloaddition reactions within SWNT showed a consistent increase in selectivity for the 1,4-triazole (up to a 55% increase). The magnitude of this effect can be tuned by varying the SWNT diameter or the steric bulk of the reactant substituents. In addition to the dominant steric factors, the results herein suggest that the electronic properties of carbon nanotubes induce an additional, more subtle influence on selectivity. Investigating the autocatalytic Soai reaction in the presence of carbon nanotubes demonstrated, on a fundamental level, that the helicity of SWNT induces an effect on the formation of chiral molecules. Since carbon nanotubes exist as a racemic mixture of P and M enantiomers, their presence has a symmetrising effect whereby an enantioselective Soai reaction affording 90% ee becomes racemic upon the addition of (6,5)-SWNT. These results clearly demonstrate the ability of carbon nanotubes to influence the properties of preparative chemical reactions.